Electronic Model of FitzHugh-Nagumo Neuron - Petrovas, A.; Lisauskas, S.; Slepikas, A. (Elektronika ir Elektrotechnika, 2012)
For investigation into neurodynamical systems FitzHugh-Nagumo model is often suggested. One neuron can be easily modeled using numerical methods, but numerical modeling of the entire network of FitzHugh-Nagumo neurons requires a lot of calculation resources and time. To overcome that problem the electronic model of FitzHugh-Nagumo neuron is proposed. The article discusses and compares some electronic models of FitzHugh-Nagumo neurons. The advantages and shortcomings of each model are discussed. Microcontroller based model of the FitzHugh-Nagumo neuron is proposed. The microcontroller calculates the nonlinear part of the FitzHugh-Nagumo equations mathematically correctly, i.e. without any approximations. Simulation results of the suggested model are presented and discussed. Ill. 4, bibl. 8 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1835